Lattice Multivariate Data Visualization with R - Sarkar, Deepayan; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
R is rapidly growing in popularity as the environment of choice for data analysis and graphics both in academia and industry. Lattice brings the proven design of Trellis graphics (originally developed for S by William S. Cleveland and colleagues at Bell Labs) to R, considerably expanding its capabilities in the process. Lattice is a powerful and elegant high level data visualization system that is sufficient for most everyday graphics needs, yet flexible enough to be easily extended to handle demands of cutting edge research. Written by the author of the lattice system, this book describes it in considerable depth, beginning with the essentials and systematically delving into specific low levels details as necessary. No prior experience with lattice is required to read the book, although basic familiarity with R is assumed. The book contains close to150 figures produced with lattice. Many of the examples emphasize principles of good graphical design; almost all use real data sets that are publicly available in various R packages. All code and figures in the book are also available online, along with supplementary material covering more advanced topics. Deepayan Sarkar won the 2004 John M. Chambers Statistical Software Award for writing lattice while he was a graduate student in Statistics at the University of Wisconsin-Madison. He is currently doing postdoctoral research in the Computational Biology program at the Fred Hutchinson Cancer Research Center, a member of the R Core Team, and an active participant on the R mailing lists.
Basics -- A Technical Overview of lattice -- Visualizing Univariate Distributions -- Displaying Multiway Tables -- Scatter Plots and Extensions -- Trivariate Displays -- Finer Control -- Graphical Parameters and Other Settings -- Plot Coordinates and Axis Annotation -- Labels and Legends -- Data Manipulation and Related Topics -- Manipulating the (3z(Btrellis(3y (BObject -- Interacting with Trellis Displays -- Extending Trellis Displays -- Advanced Panel Functions -- New Trellis Displays -- Color Plates.s
Keywords: Mathematics; Computer graphics; Visualization; Discrete mathematics; Statistics; Mathematics; Discrete Mathematics; Statistics and Computing/Statistics Programs; Visualization; Computer Graphics; Electronic books